Evaluation Of The Combined Effects Of Long Term Aging And Moisture Damage On Asphalt Mixture Incorporating Cubical Aggregates And Zycotherm - Tan, Shin Ru (Universiti Sains Malaysia, 2018)
Warm mix asphalt (WMA) is a sustainable technology developed to lower the mixing and compaction temperatures but can be prepared using conventional asphalt plant and paving machineries. In terms of environmental and sustainability aspects, WMA can effectively reduce greenhouse gas emissions. Due to its lower production temperature, WMA is more prone to moisture damage due to incomplete drying of aggregate thus results in trapped moisture. Excessive intrusion of moisture into the asphalt pavement would deteriorate the pavement quality and have adverse impact on asphalt pavement. A warm compaction additive from India named Zycotherm was added to produce WMA and its effectiveness as an anti-stripping agent was investigated. To simulate the actual condition on site, the asphalt mixtures were subjected to simultaneously long term aging and moisture damage. The performance of WMA and HMA were evaluated in terms of compactability, workability, tensile and shear strengths. From the investigation, WMA can be more easily compacted and more workable compared to HMA. WMA exhibited better moisture resistance after subjected to moisture conditioning. The utilization of cubical aggregates in asphalt mixture showed better performance in terms of tensile and shear stresses. From image analysis, WMA incorporating cubical aggregates demonstrated lower percentage adhesive failure which proved the effectiveness of Zycotherm. The formation of fractured aggregates was primarily due to the aggregate shape instead of aggregate orientation. This is because most of the broken aggregates were elongated or flaky normal aggregates that breaks easily along their weak plane when subjected to applied loads. Analysis on the aggregate gradation after compaction and performance tests proved that cubical aggregates degraded less than normal aggregates.